Socialization of the Roles and Functions of Export Financing Institutions Indonesia (LPEI) in Supporting Potential Commodity Exports Lampung Province for MSME Activists in Bandar Lampung: Sosialisasi Peran dan Fungsi Lembaga Pembiayaan Ekspor Indonesia (LPEI) dalam Mendukung Ekspor Komoditas Potensial Provinsi Lampung Bagi Para Pegiat UMKM Di Bandar Lampung - Roby Rakhmadi; Nibras Fadhillah; Agus Hadiawan (Program Studi Hubungan Internasional FISIP UNILA, 2023)
International trade has now become an important activity of a country in boosting its economy. In particular, in the current era of globalization, every country in the world is required to be able to compete for markets in the world. Therefore, economic improvement through the growth of the Micro, Small and Medium Enterprises (MSMEs) sector is one of the alternative solutions in the midst of today's competitive market competition. MSMEs are required to be able to survive and compete with their people's economic pattern in the midst of competitive competition with various large multinational companies. What's more, after the Covid-19 pandemic which had a significant impact on the world economy, many changes were made as an adaptation to recover the economy and rise to compete in an increasingly competitive trade. This economic adaptation also includes how MSMEs and cooperatives run their business units in an effort to survive financially. This Community Service activity uses the method of delivering material from various sources, activists of exportimport activities and academics. The survey method was also carried out to see the knowledge of young MSMEs in Bandar Lampyng related to international business and export-import activities. The external plan for this activity is publication in the LPPM service journal, University of Lampung.